A pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system and a pre-filming process thereof

By using phosphorus-free prefiltering agent compositions, including tripolymer thiocyanic acid, 8-hydroxyquinoline, AA/AMPS, aluminum salt and zinc salt in the circulating water system, the problems of low corrosion resistance and long film formation time in the prior art are solved, and fast and effective anti-corrosion treatment of metal surfaces are achieved, and suitable for a wide range of circulating water systems.

CN118854275BActive Publication Date: 2025-03-21SHANGHAI SUNUO ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411321407.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing anti-corrosion treatment methods for metal surfaces in circulation water systems have problems such as low corrosion resistance, long film formation time, high water quality requirements and limited application range.

Method used

A phosphorus-free prefilm agent composition is adopted, including tripolymer thiocyanic acid or its salt, 8-hydroxyquinoline, AA/AMPS, aluminum salt and zinc salt, and by bonding with metal ions, a stable and dense corrosion-resistant layer is formed to achieve rapid film formation and high corrosion resistance.

Benefits of technology

It realizes the rapid formation of corrosion-resistant layers with excellent corrosion resistance in the circulating water system, and the film formation time can be as low as 20 hours or even 10 hours. It is suitable for all types of circulating water systems and has low water quality requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854275B_ABST
    Figure CN118854275B_ABST
Patent Text Reader

Abstract

The present application provides a pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system, including thiocyanuric acid or thiocyanuric acid salt, 8-hydroxyquinoline, AA / AMPS, aluminum salt and zinc salt. The present application also provides a pre-filming process using the above-mentioned pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system, comprising the following steps: Step 1): inject water into the cleaned circulating water system, turn on the circulation pump to circulate the water; Step 2): add thiocyanuric acid or thiocyanuric acid salt, 8-hydroxyquinoline, AA / AMPS to the circulating water, adjust the pH, add aluminum salt and zinc salt, and pre-film. The present application is a pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system, and the components are all phosphorus-free components, which are relatively friendly to the environment. When the metal surface of the circulating water system is treated for anti-corrosion, the film forming speed is fast, the pre-filming time is short, and the corrosion-resistant layer formed by the pre-filming has excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal surface treatment in circulating cooling water systems, and in particular to a pre-filming agent composition for anti-corrosion treatment of metal surfaces in circulating water systems and a pre-filming process thereof. Background Art

[0002] After the circulating water system is cleaned, the metal surfaces in the system are in an activated state. Before it is put back into use, in order to prevent the metal from corroding quickly, a complete, corrosion-resistant protective film needs to be pre-generated on these metal surfaces.

[0003] The most classic pre-filming method is phosphorus-zinc pre-filming, which has a fast film-forming speed and strong corrosion resistance. However, with the increasing environmental protection requirements, this phosphorus-containing pre-filming method is restricted in many occasions. In recent years, a series of phosphorus-free pre-filming methods have emerged, but they all have some disadvantages. The common disadvantage is that the corrosion resistance is poorer than that of phosphorus-zinc pre-filming. Other disadvantages include: the formula containing tungstate is expensive; the film-forming speed of the sodium gluconate / sodium polyacrylate formula is too slow, it takes several days to complete, and it is not suitable for all types of metals and cooling water systems; the polyepoxysuccinic acid / zinc salt formula requires precise control of the proportion of each component to ensure the pre-filming effect, but zinc salt easily forms precipitation in water, and it is difficult to achieve the expected ratio, so the water quality requirements for pre-filming are very high, which limits the scope of application, and this formula also has the disadvantage of long film-forming time.

[0004] Therefore, it is very necessary to provide an environmentally friendly pre-filming agent and a pre-filming process thereof, which has a short pre-filming time and good pre-filming effect when performing anti-corrosion treatment on the metal surface of a circulating water system. Summary of the invention

[0005] The present invention is a phosphorus-free combination solution, which forms a stable, dense and durable anti-corrosion layer by bonding with water ions or metal materials through groups (such as mercapto-HS, dithiocarboxyl-CSSH, etc.) with strong complexing and coordination capabilities with metal ions and metal materials. The film-forming time can be as low as 20 hours or even within 10 hours. The corrosion resistance of the film is better than that of the phosphorus-zinc pre-filming effect, and it is suitable for pre-filming of all circulating water systems.

[0006] In order to solve at least one of the above technical problems, in the first aspect of the present application, the present application provides a pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system, comprising thiocyanuric acid or thiocyanurate, 8-hydroxyquinoline, AA / AMPS, aluminum salt and zinc salt.

[0007] Through the above technical solution, thiocyanuric acid or its salt can form a planar network structure with aluminum ions, zinc ions, ferrous ions and trivalent iron ions in water, and deposit on the metal surface to protect the metal material; the redundant coordination groups in the planar structure directly coordinate with the metal substrate to form a strong coordination bond, which increases the bonding force between the planar structure and the metal substrate, making the bonding between the two very strong, and increasing the corrosion resistance and corrosion resistance durability. Figure 1 shown.

[0008] Under the synergistic effect of zinc, aluminum and other ions, thiocyanuric acid or its salt directly combines with the metal substrate to form small protective units, and then fills the defects of the surface structure with deposits such as zinc hydroxide, aluminum hydroxide, and the complex products of 8-hydroxyquinoline and zinc or aluminum, making the film more complete. The protective small units formed by thiocyanuric acid or its salt, 8-hydroxyquinoline and zinc or aluminum can form coordination with the metal substrate, so the fastness is greatly improved, thereby increasing the anti-corrosion performance and anti-corrosion durability.

[0009] Trithiocyanate or its salts have a strong ability to stabilize zinc ions and aluminum ions. When metal materials are corroded, the ferrous ions produced and the trivalent ferrous ions they are converted into can squeeze out the coordination positions originally occupied by zinc ions or aluminum ions, replacing the aluminum ions or zinc ions, and then forming sediments to fill the "wounds" of the corroded areas of the metal materials, thereby playing an anti-corrosion role.

[0010] Preferably, the usage ratio of thiocyanuric acid or thiocyanurate, 8-hydroxyquinoline, AA / AMPS, aluminum salt and zinc salt is 0.1-10 mmol:0.01-10 mmol:10-200 mg:0.01-10 mmol:0.01-10 mmol, the aluminum salt is aluminum sulfate or aluminum chloride, the zinc salt is zinc sulfate or zinc chloride, and the thiocyanurate is trisodium thiocyanurate.

[0011] In a second aspect of the present application, the present application provides a pre-filming process using the pre-filming agent composition for anti-corrosion treatment of metal surfaces in a circulating water system according to the first aspect of the present application, comprising the following steps:

[0012] Step 1): Inject water into the cleaned circulating water system, turn on the circulation pump, and allow the water to circulate;

[0013] Step 2): Add thiocyanuric acid or thiocyanurate, 8-hydroxyquinoline, AA / AMPS to the circulating water, adjust the pH, add aluminum salt and zinc salt, and pre-film.

[0014] Preferably, in step 1), the turbidity of water is controlled to be less than 30 NTU, the total iron is controlled to be less than 3 ppm, the flow rate of water is 1.0-1.5 m / s, and the temperature of water is 15-50°C.

[0015] Preferably, in step 2), the concentration of thiocyanuric acid or thiocyanurate is controlled to be 0.1-10 mmol / L, the concentration of 8-hydroxyquinoline is controlled to be 0.01-10 mmol / L, and the concentration of AA / AMPS is controlled to be 10-200 ppm.

[0016] Preferably, in step 2), the ratio of thiocyanuric acid or thiocyanuric acid salt, 8-hydroxyquinoline, AA / AMPS, aluminum salt and zinc salt added is 0.1-10 mmol:0.01-10 mmol:10-200 mg:0.01-10 mmol:0.01-10 mmol.

[0017] Preferably, in step 2), the zinc salt is added in 2-5 times, and the ratio of the amount of the zinc salt added for the first time to the amount of the zinc salt added for the second time is 0.75-6:1.

[0018] Preferably, the time interval between the first addition of the zinc salt and the second addition of the zinc salt is 4-12 h.

[0019] Preferably, in the step 2), the aluminum salt is added in 2-5 times, and the ratio of the amount of the aluminum salt added in the first time to that in the second time is 1-5:1.

[0020] Preferably, in step 2), the pH is adjusted to 5.5-7.5, preferably 5.5-6.5.

[0021] Preferably, the pre-filming time is controlled to be 4-24 h.

[0022] In summary, the present invention includes at least one of the following beneficial technical effects:

[0023] 1. The pre-filming agent composition for anti-corrosion treatment of metal surfaces in the circulating water system provided in the present application is a phosphorus-free formula and is relatively environmentally friendly.

[0024] 2. The pre-filming agent composition for anti-corrosion treatment of metal surfaces in circulating water systems provided in the present application has a fast film-forming speed when performing anti-corrosion treatment on metal surfaces in circulating water systems. An anti-corrosion layer with excellent corrosion resistance can be formed within 20 hours or even within 10 hours. Extending the pre-filming time will have a better effect.

[0025] 3. The pre-filming agent composition for anti-corrosion treatment of metal surfaces in circulating water systems provided in the present application has excellent anti-corrosion performance when used for anti-corrosion treatment of metal surfaces in circulating water systems. Through the copper sulfate titration test on the hanging pieces, the longest color change time of the hanging pieces with a pre-filming time of less than 10 hours is 56 seconds, which is far exceeding the 10s required by the specification. In the embodiment of the present invention, when the pre-filming agent composition for anti-corrosion treatment of metal surfaces in circulating water systems is used for anti-corrosion treatment of metal surfaces in circulating water systems, the longest color change time of the hanging pieces with a pre-filming time of more than 10 hours reaches 82 seconds.

[0026] 4. The pre-coating scheme for anti-corrosion treatment of metal surfaces in the circulating water system of this application has lower requirements for water quality during pre-coating. The turbidity and total iron requirements are lower than those of phosphorus-zinc pre-coating, and there are no special requirements for hardness, so it has a wide range of applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the pre-filming of the anti-corrosion pre-filming agent composition for metal surfaces in the circulating water system of this application;

[0028] In the figure, M represents other metal ions in water besides zinc ions and aluminum ions, such as iron ions, calcium ions, magnesium ions, copper ions, etc. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific examples, but the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.

[0030] In the examples, AA / AMPS is acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, purchased from Shandong Taihe Water Treatment Technology Co., Ltd.

[0031] Example 1

[0032] Adjust the water level of the cleaned circulating water system to the minimum safe circulating water level. The water turbidity of the system is 24.6NTU, the total iron is 1.8ppm, the water temperature is 27℃, and the water flow rate is 1.5m / s. Put in the cleaned A3Ⅱ type hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS (acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer) dissolved in tap water in advance (based on the complete dissolution of trisodium thiocyanate, 8-hydroxyquinoline and AA / AMPS, and no solid matter visible to the naked eye). The concentration of trisodium thiocyanate added is 3mmol / L, the concentration of 8-hydroxyquinoline added is 1.5mmol / L, and the concentration of AA / AMPS added is 1. 50ppm, that is, the concentration of trisodium thiocyanate in the circulating water system is increased by 3mmol / L, the concentration of 8-hydroxyquinoline is increased by 1.5mmol / L, and the concentration of AA / AMPS is increased by 150ppm. After uniform circulation, the pH value is adjusted to 6.0, and then zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water are added (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate and no solid matter visible to the naked eye). The addition concentration of zinc sulfate heptahydrate is 1mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 0.5mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1mmol / L, and the concentration of aluminum sulfate is increased by 0.5mmol / L, and the timing pre-filming is started. After 5 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water were added (the zinc sulfate heptahydrate and aluminum sulfate 18hydrate were completely dissolved and no solid matter was visible to the naked eye). The concentration of zinc sulfate heptahydrate was 0.2mmol / L (the concentration of zinc sulfate in the system increased by 0.2mmol / L), and the concentration of aluminum sulfate 18hydrate was 0.1mmol / L (the concentration of aluminum sulfate in the system increased by 0.1mmol / L). After the total pre-filming time was 7 hours, heptahydrate dissolved in tap water was added. Zinc and aluminum sulfate 18hydrate (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate and no visible solid matter), the addition concentration of zinc sulfate heptahydrate is 0.2mmol / L (so that the concentration of zinc sulfate in the system increases by 0.2mmol / L), the addition concentration of aluminum sulfate 18hydrate is 0.1mmol / L (so that the concentration of aluminum sulfate in the system increases by 0.1mmol / L), keep the pH at 6.0 during the pre-filming period, continue the pre-filming for 3h, that is, the total pre-filming time is 10h, take out the coupon, rinse and dry it, and mark the coupon as coupon 1.

[0033] Example 2

[0034] Adjust the water level of the cleaned circulating water system to the minimum safe circulating water level. The water turbidity of the system is 10.5 NTU, the total iron is 1.2 ppm, the water temperature is 31 ° C, and the water flow rate is 1.5 m / s. Put in the cleaned A3Ⅱ type hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS dissolved in tap water in advance (trisodium thiocyanate, 8-hydroxyquinoline and AA / AMPS are completely dissolved and there is no solid matter visible to the naked eye) to the circulating water system. The concentration of trisodium thiocyanate added is 4m mol / L, 8-hydroxyquinoline addition concentration is 0.4mmol / L, AA / AMPS addition concentration is 120ppm. After uniform circulation, adjust the pH value to 5.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance to the circulating water system (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate and no solid matter visible to the naked eye), among which the addition concentration of zinc sulfate heptahydrate is 1.2mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 0.8mmol / L, and start timing pre-filming. After 4 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (when zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 0.3mmol / L and the concentration of aluminum sulfate 18hydrate is 0.2mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 0.3mmol / L and the concentration of aluminum sulfate is increased by 0.2mmol / L, and the pH is maintained at 5.5 during the pre-filming period; the pre-filming is continued for 4 hours, that is, the total pre-filming time is 8 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 2.

[0035] Example 3

[0036] Adjust the water level of the cleaned circulating water system to the minimum safe circulating water level. The water turbidity of the system is 6.3NTU, the total iron is 0.7ppm, the water temperature is 35℃, and the water flow rate is 1.0m / s. Put in the cleaned A3Ⅱ type hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS dissolved in tap water in advance (trisodium thiocyanate, 8-hydroxyquinoline and AA / AMPS are completely dissolved and there is no solid matter visible to the naked eye) to the circulating water system. The concentration of trisodium thiocyanate is 2mmol / L, the concentration of 8-hydroxyquinoline is 2mmol / L, and the concentration of AA / AMPS is 2mmol / L. The MPS addition concentration is 200ppm. After uniform circulation, the pH value is adjusted to 6.5. Then, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance are added to the circulating water system (the zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and there is no solid matter visible to the naked eye). The addition concentration of zinc sulfate heptahydrate is 0.5mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 1.5mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 0.5mmol / L, and the concentration of aluminum sulfate is increased by 1.5mmol / L. The timing of pre-filming is started, and the pH is kept at 6.5 during the pre-filming period. The total pre-filming time is 15h, and the hanging piece is taken out, rinsed and dried. The hanging piece is marked as hanging piece 3.

[0037] Example 4

[0038] Adjust the water level of the cleaned circulating water system to the minimum safe circulating water level. The water turbidity of the system is 21.4 NTU, the total iron is 2.3 ppm, the water temperature is 22°C, and the water flow rate is 1.5 m / s. Put in the cleaned A3Ⅱ type hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS dissolved in tap water in advance (trisodium thiocyanate, 8-hydroxyquinoline and AA / AMPS are completely dissolved and there is no solid matter visible to the naked eye) to the circulating water system. The concentration of trisodium thiocyanate added is 2.5 mmol / L, and the concentration of 8-hydroxyquinoline added is 1.5 mmol / L, AA / AMPS addition concentration is 80ppm. After uniform circulation, adjust the pH value to 6.0, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance to the circulating water system (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate and no solid matter visible to the naked eye), among which the addition concentration of zinc sulfate heptahydrate is 1.8mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 0.2mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1.8mmol / L, and the concentration of aluminum sulfate is increased by 0.2mmol / L, and the timing pre-filming starts. After 8 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (the zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added to the circulating water system, wherein the concentration of zinc sulfate heptahydrate is 0.6mmol / L and the concentration of aluminum sulfate 18hydrate is 0.1mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 0.6mmol / L and the concentration of aluminum sulfate is increased by 0.1mmol / L. During the pre-filming, the pH is kept at 6.0; the pre-filming is continued for 8 hours, that is, the total pre-filming time is 16 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 4.

[0039] Example 5

[0040] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0041] The test parameters are as follows:

[0042] The test water was Nanjing tap water, the water turbidity was adjusted to 30 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 3 ppm, the water temperature was 15 °C, and the water flow rate was 1.5 m / s.

[0043] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ type hanging plate, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS that were dissolved in tap water in advance (the concentration of trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS is 6.0mmol / L, the concentration of 8-hydroxyquinoline is 0.01mmol / L, and the concentration of AA / AMPS is 10ppm. After even circulation, , adjust the pH value to 7.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye) to the circulating water system. The concentration of zinc sulfate heptahydrate is 0.01mmol / L, and the concentration of aluminum sulfate 18hydrate is 4.0mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 0.01mmol / L, and the concentration of aluminum sulfate is increased by 4.0mmol / L, and the timing of pre-filming begins. After 10 hours of pre-filming, add aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye), and the concentration of aluminum sulfate 18hydrate is 1.0mmol / L. Keep the pH at 7.5 during the pre-filming period; continue pre-filming for 10 hours, that is, the total pre-filming time is 20 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 5.

[0044] Example 6

[0045] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0046] The test parameters are as follows:

[0047] The test water was Nanjing tap water, the water turbidity was adjusted to 5.2 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.0 ppm, the water temperature was 35°C, and the water flow rate was 1.5 m / s.

[0048] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS that have been dissolved in tap water in advance (the concentration of trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS is 5.0mmol / L, the concentration of 8-hydroxyquinoline is 0.3mmol / L, and the concentration of AA / AMPS is 150ppm. After the ring is uniform, adjust the pH value to 6.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate which have been dissolved in tap water in advance (based on the fact that zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and there is no solid matter visible to the naked eye). The addition concentration of zinc sulfate heptahydrate is 2.0mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 1.0mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 2.0mmol / L, and the concentration of aluminum sulfate is increased by 1.0mmol / L, and the timing of pre-filming begins. After 6 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (when zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 1.0mmol / L and the concentration of aluminum sulfate 18hydrate is 0.5mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1.0mmol / L and the concentration of aluminum sulfate is increased by 0.5mmol / L, and the pH is maintained at 6.5 during the pre-filming period; the pre-filming is continued for 6 hours, that is, the total pre-filming time is 12 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 6.

[0049] Example 7

[0050] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0051] The test parameters are as follows:

[0052] The test water was Nanjing tap water, the water turbidity was adjusted to 10 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 0.5 ppm, the water temperature was 50°C, and the water flow rate was 1.2 m / s.

[0053] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ type hanging plate, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS that were dissolved in tap water in advance (trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS are completely dissolved and there is no solid matter visible to the naked eye). The concentration of trisodium thiocyanate is 0.1mmol / L, the concentration of 8-hydroxyquinoline is 10mmol / L, and the concentration of AA / AMPS is 180ppm. The circulation is evenly distributed. After mixing, adjust the pH value to 5.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye), wherein the concentration of zinc sulfate heptahydrate is 2.0mmol / L, and the concentration of aluminum sulfate 18hydrate is 0.01mol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 2.0mmol / L, and the concentration of aluminum sulfate is increased by 0.01mmol / L, and the timing of pre-filming is started. Keep the pH at 5.5 during the pre-filming period; the total pre-filming time is 4h. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 7.

[0054] Example 8

[0055] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0056] The test parameters are as follows:

[0057] The test water was Nanjing tap water, the water turbidity was adjusted to 8.9 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.5 ppm, the water temperature was 18°C, and the water flow rate was 1.5 m / s.

[0058] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ type hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS that were dissolved in tap water in advance (the concentration of trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS is 10.0mmol / L, the concentration of 8-hydroxyquinoline is 0.2mmol / L, and the concentration of AA / AMPS is 150ppm. Circulate for 2 hours. After uniformity, adjust the pH value to 6.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate which have been dissolved in tap water in advance (based on the fact that zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and there is no solid matter visible to the naked eye), wherein the addition concentration of zinc sulfate heptahydrate is 2.0mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 1.0mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 2.0mmol / L, and the concentration of aluminum sulfate is increased by 1.0mmol / L, and the timing of pre-filming is started. After 12 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (the zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 1.5mmol / L and the concentration of aluminum sulfate 18hydrate is 0.5mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1.5mmol / L and the concentration of aluminum sulfate is increased by 0.5mmol / L, and the pH is maintained at 6.5 during the pre-filming period; the pre-filming is continued for 12 hours, that is, the total pre-filming time is 24 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 8.

[0059] Example 8-1

[0060] The difference between Example 8-1 and Example 8 is that the concentration of zinc sulfate heptahydrate added for the first time is 3.0 mmol / L, and the concentration of zinc sulfate heptahydrate added for the second time is 0.5 mmol / L. The hanging piece is marked as hanging piece 8-1.

[0061] Example 8-2

[0062] The difference between Example 8-2 and Example 8 is that the concentration of zinc sulfate heptahydrate added for the first time is 1.5 mmol / L, and the concentration of zinc sulfate heptahydrate added for the second time is 2.0 mmol / L. The hanging piece is marked as hanging piece 8-2.

[0063] Example 8-3

[0064] The difference between Example 8-3 and Example 8 is that the pH value is adjusted to 5.0 and maintained at 5.0 during the pre-filming period. The coupon is labeled as coupon 8-3.

[0065] Example 8-4

[0066] The difference between Example 8-4 and Example 8 is that the concentration of trisodium thiocyanate added is 9.9 mmol / L and the concentration of 8-hydroxyquinoline added is 0.3 mmol / L. The coupon is marked as coupon 8-4.

[0067] Example 8-5

[0068] The difference between Example 8-5 and Example 8 is that zinc sulfate heptahydrate and aluminum sulfate 18hydrate are added for the second time 8 hours after the pre-filming, and the pre-filming is continued for 16 hours after the addition, and the total pre-filming time is 24 hours. The coupon is marked as coupon 8-5.

[0069] Example 9

[0070] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0071] The test parameters are as follows:

[0072] The test water was Nanjing tap water, the water turbidity was adjusted to 3.2 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 0.8 ppm, the water temperature was 32°C, and the water flow rate was 1.5 m / s.

[0073] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ hanging plate, and start adding thiocyanuric acid, 8-hydroxyquinoline, and AA / AMPS that were dissolved in tap water in advance (the concentration of trisodium thiocyanurate, 8-hydroxyquinoline, and AA / AMPS is 0.1mmol / L, the concentration of 8-hydroxyquinoline is 10mmol / L, and the concentration of AA / AMPS is 150ppm. Circulate evenly. After that, adjust the pH value to 5.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate which have been dissolved in tap water in advance (based on the fact that zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and there is no solid matter visible to the naked eye), wherein the addition concentration of zinc sulfate heptahydrate is 5.0mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 0.1mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 5.0mmol / L, and the concentration of aluminum sulfate is increased by 0.1mmol / L, and the timing of pre-filming is started. After 7 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (the zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 5.0mmol / L and the concentration of aluminum sulfate 18hydrate is 0.1mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 5.0mmol / L and the concentration of aluminum sulfate is increased by 0.1mmol / L, and the pH is maintained at 5.5 during the pre-filming period; the pre-filming is continued for 7 hours, that is, the total pre-filming time is 14 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 9.

[0074] Example 10

[0075] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0076] The test parameters are as follows:

[0077] The test water was Nanjing tap water. The water turbidity was adjusted to 6.5 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.2 ppm, the water temperature was 23 °C, and the water flow rate was 1.5 m / s.

[0078] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ type hanging plate, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS dissolved in tap water in advance (based on the complete dissolution of trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS, and no solid matter visible to the naked eye). The addition concentration of trisodium thiocyanate is 2.0 mmol / L, the addition concentration of 8-hydroxyquinoline is 1.2 mmol / L, and the addition concentration of AA / AMPS is 170 ppm. After uniform circulation, adjust the pH value to 6.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye). The addition concentration of zinc sulfate heptahydrate is 0.2 mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 5.0 mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 0.2 mmol / L, the concentration of aluminum sulfate increased by 5.0mmol / L, and the timing of pre-filming began. After 8 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, with no visible solid matter) were added, where the concentration of zinc sulfate heptahydrate was 0.2 mmol / L, and the concentration of aluminum sulfate 18hydrate was 5.0 mmol / L, that is, the concentration of zinc sulfate in the circulating water system increased by 0.2 mmol / L, and the concentration of aluminum sulfate increased by 5.0 mmol / L, and the pH was kept at 6.5 during the pre-filming period; the pre-filming was continued for 8 hours, that is, the total pre-filming time was 16 hours. Take out the coupon, rinse and dry it, and mark the coupon as coupon 10.

[0079] Embodiment 11

[0080] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0081] The test parameters are as follows:

[0082] The test water was Nanjing tap water, the water turbidity was adjusted to 12.4 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.3 ppm, the water temperature was 30 °C, and the water flow rate was 1.5 m / s.

[0083] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ hanging piece, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS that were dissolved in tap water in advance (trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS are completely dissolved and there is no solid matter visible to the naked eye). The concentration of trisodium thiocyanate added is 2.3mmol / L, the concentration of 8-hydroxyquinoline added is 0.78mmol / L, and the concentration of AA / AMPS added is 150mmol / L. ppm, after uniform circulation, adjust the pH value to 6.0, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate which are dissolved in tap water in advance (based on the fact that zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and there is no solid matter visible to the naked eye), wherein the addition concentration of zinc sulfate heptahydrate is 2.0mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 1.0mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 2.0mmol / L, and the concentration of aluminum sulfate is increased by 1.0mmol / L, and the timing of pre-filming is started. After 6 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water (when zinc sulfate heptahydrate and aluminum sulfate 18hydrate are completely dissolved and no solid matter is visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 1.0mmol / L and the concentration of aluminum sulfate 18hydrate is 0.5mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1.0mmol / L and the concentration of aluminum sulfate is increased by 0.5mmol / L, and the pH is maintained at 6.0 during the pre-filming period; the pre-filming is continued for 5 hours, that is, the total pre-filming time is 11 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 11.

[0084] Example 12

[0085] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0086] The test parameters are as follows:

[0087] The test water was Nanjing tap water, the water turbidity was adjusted to 8.9 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.5 ppm, the water temperature was 20 °C, and the water flow rate was 1.5 m / s.

[0088] After preparing the water according to the above parameters, put in the cleaned A3Ⅱ type hanging plate, and start adding trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS dissolved in tap water in advance (based on the complete dissolution of trisodium thiocyanate, 8-hydroxyquinoline, and AA / AMPS, and no solid matter visible to the naked eye). The addition concentration of trisodium thiocyanate is 5.0 mmol / L, the addition concentration of 8-hydroxyquinoline is 2.0 mmol / L, and the addition concentration of AA / AMPS is 100 ppm. After evenly circulating, adjust the pH value to 6.5, and then add zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye). The addition concentration of zinc sulfate heptahydrate is 3.0 mmol / L, and the addition concentration of aluminum sulfate 18hydrate is 1.0 mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 3.0mmol / L, and the concentration of aluminum sulfate is increased by 1.0 mmol / L, and the timing of pre-filming begins. After 10 hours of pre-filming, zinc sulfate heptahydrate and aluminum sulfate 18hydrate dissolved in tap water in advance (based on the complete dissolution of zinc sulfate heptahydrate and aluminum sulfate 18hydrate, and no solid matter visible to the naked eye) are added, wherein the concentration of zinc sulfate heptahydrate is 1.5 mmol / L, and the concentration of aluminum sulfate 18hydrate is 0.5 mmol / L, that is, the concentration of zinc sulfate in the circulating water system is increased by 1.5 mmol / L, and the concentration of aluminum sulfate is increased by 0.5 mmol / L, and the pH is maintained at 6.5 during the pre-filming period; continue pre-filming for 10 hours, that is, the total pre-filming time is 20 hours. Take out the hanging piece, rinse and dry it, and mark the hanging piece as hanging piece 12.

[0089] Example 13

[0090] Comparative experiment: phosphorus-zinc pre-filming

[0091] The evaluation test equipment refers to HG / T 2160-91: Cooling water dynamic simulation test method.

[0092] The test parameters are as follows:

[0093] The test water was Nanjing tap water, the water turbidity was adjusted to 5.3 NTU with diatomaceous earth and ammonium ferrous sulfate, the total iron was 1.2 ppm, the water temperature was 18°C, the water flow rate was 1.5 m / s, and the calcium ion concentration was 80 ppm.

[0094] After preparing water according to the above parameters, put in the cleaned A3Ⅱ type coupon, and start adding sodium hexametaphosphate and zinc sulfate monohydrate dissolved in tap water in advance, where the addition of sodium hexametaphosphate is 640 ppm and the addition of zinc sulfate monohydrate is 160 ppm. After even circulation, adjust the pH value to 6.5, and the pre-filming time is 48 hours, during which the pH value is controlled at about 6.5. Take out the coupon, rinse and dry it, and mark the coupon as coupon 13.

[0095] Comparative Example 1

[0096] The difference between Comparative Example 1 and Example 8 is that 8-hydroxyquinoline is not added.

[0097] Comparative Example 2

[0098] The difference between Comparative Example 2 and Example 8 is that no AA / AMPS is added. The coupon is marked as coupon 15.

[0099] Comparative Example 3

[0100] The difference between Comparative Example 3 and Example 8 is that trisodium thiocyanate is not added.

[0101] The coupons 1-16 and coupons 8-(1-5) obtained in Example 1-13, Comparative Example 1-3 and Example 8-(1-5) were subjected to a pre-filming effect test - a copper sulfate spot test, and the steps are as follows:

[0102] a. Solution preparation: Add 15 g NaCl and 5 g copper sulfate pentahydrate into 100 mL distilled water and stir well.

[0103] b. Spot test: Use the solution prepared in step a to drop on the pre-filmed coupon and record the time (in seconds) required for the blue spot to turn red. The results are shown in Table 1.

[0104] Table 1 Test results of pre-filming effect of hanging pieces 1-16 and hanging pieces 8-(1-5)

[0105]

[0106] As shown in the table above, except for Example 8-3 in which the pH value was too low and the color change time was less than 10 s, the anti-corrosion pre-filming process for the metal surface of the circulating water system in other examples exceeded the standard requirement of 10 s, and the results of half of the examples were better than the 51 s color change time of the phosphorus-zinc pre-filmed comparison hanging piece, among which the best was Example 8, in which the color change time of copper sulfate on the hanging piece reached 82 s, and the color change time of copper sulfate on the hanging piece of Example 1 in which the total pre-filming time was less than 10 hours also reached 56 s.

[0107] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A pre-filming process, characterized in that: The steps include: Step 1): Inject water into the cleaned circulating water system, turn on the circulation pump, and allow the water to circulate; Step 2): Add thiocyanuric acid or thiocyanurate, 8-hydroxyquinoline and AA / AMPS to the circulating water, adjust the pH, add aluminum salt and zinc salt, and pre-film; In the step 2), the concentration of thiocyanuric acid or thiocyanate is controlled to be 0.1-10 mmol / L, the concentration of 8-hydroxyquinoline is controlled to be 0.01-10 mmol / L, and the concentration of AA / AMPS is controlled to be 10-200 ppm; In the step 2), the pH is adjusted to 5.5-7.

5.

2. The pre-filming process according to claim 1, characterized in that: In the step 2), the ratio of thiocyanuric acid or thiocyanuric acid salt, 8-hydroxyquinoline, AA / AMPS, aluminum salt and zinc salt added is 0.1-10 mmol: 0.01-10 mmol: 10-200 mg: 0.01-10 mmol: 0.01-10 mmol.

3. The pre-filming process according to claim 1, characterized in that: In the step 2), the zinc salt is added in 2-5 times, and the molar ratio of the zinc salt added for the first time to the zinc salt added for the second time is 0.75-6:

1.

4. The pre-filming process according to claim 3, characterized in that: The time interval between the first addition of zinc salt and the second addition of zinc salt is 4-12 h.

5. The pre-filming process according to claim 1, characterized in that: In the step 2), the aluminum salt is added in 2-5 times, and the ratio of the amount of the aluminum salt added for the first time to the amount added for the second time is 1-5:

1.

6. The pre-filming process according to claim 1, characterized in that: Control the pre-filming time to 4-24 h.

Citation Information

Patent Citations

  • Phosphorus-free pre-filming agent based on sulfo group as well as preparation method and application of phosphorus-free pre-filming agent

    CN117165931A